Sophie Van Bijsterveld, The Empty Throne, Democracy and the Rule of Law in Transition, Lemma, Utrecht 2003, 378 σελ. - Ακριβοπούλου Χριστίνα (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
[Δε διατίθεται περίληψη / no abstract available]